Ultrasound diagnosis of adenomyosis, leiomyoma, or combined with histopathological correlation - Magdi Hanafi (Wolters Kluwer Medknow Publications, 2013)
Objective: To evaluate the accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the diagnosis of adenomyosis, leiomyoma, or combined adenomyosis and leiomyoma by the use of transvaginal ultrasonography (TVS) compared to the histopathological findings. Subjects and Methods: This is a retrospective study of patients with a preoperative TVS diagnosis of adenomyosis, leiomyoma, or combined. Patients diagnosed with adenomyosis or combined adenomyosis and leiomyoma via TVS underwent hysterectomy. Symptomatic patients diagnosed with adenomyosis and leiomyoma via TVS underwent myomectomy with excision of the surrounding myometrium which contained possible adenomyosis. Following surgery, a histopathological examination was performed by the hospital pathologists. The microscopic diagnosis of the specimen was recorded. Results: TVS diagnosis of adenomyosis was sensitive but not specific. TVS was sensitive, specific, and accurate in the diagnosis of leiomyoma and combined adenomyosis and leiomyoma. Conclusion: This study demonstrated that TVS is a valuable noninvasive method that should be utilized in the diagnosis of leiomyoma and combined adenomyosis and leiomyoma. TVS is sensitive, but is not specific in the diagnosis of adenomyosis only.